Respon Pertumbuhan Tanaman Sawi Caisim (Brassic juncea L) Terhadap Aplikasi Berbagai Macam Pupuk Organik - mitha miftahul jannah; Nurhidayati Nurhidayati; Siti Muslikah (AGRONISMA, 2022)
Caisim is one type of leaf vegetable that is favored by Indonesian consumers because it contains various nutrients that are nutritious for health. This study aims to compare the effect of using several types of organic fertilizers compared to inorganic fertilizers on the growth of caisim mustard plants. This study used a Simple Randomized Block Design (RAK). There are 7 types of treatment, including: P0 = No fertilizer application, P1 = NPK fertilizer 1 gram per pot, P2 = Compost fertilizer, P3 = Cow manure, P4 = Chicken manure, P5 = Vermicompost fertilizer, and P6 = Vermicompost nano fertilizer. The dose of organic fertilizer applied is equivalent to the N content of NPK fertilizer. The resulting data were analyzed (F test variety) with a level of 5% to determine the effect of treatment. If the results of the F test have a significant effect, then continue with the further BNT test with a level of 5% to determine the effect of growth on plant yields. The results showed that in general the P6 treatment (nano vermicompost fertilizer) gave the best growth response on the variable number of leaves and leaf area. Based on the research that has been done, it is recommended that in the cultivation of mustard caisim the right fertilizer is used, namely nano vermicompost fertilizer.Â Keywords: Caisim, Nano vermicompost, Growth response